An analysis of the characteristics of firms and universities in shaping geographical distance of university-industry linkages - Garcia Renato; Araujo Veneziano; Mascarini Suelene; Santos Emerson; Costa Ariana (European Regional Science Association (ERSA), 2015)
University has being playing an increasing role in supporting innovation. In this way, university-industry linkages has become a growing subject in the literature, in order to understand how these relationships are shaped on space. Recent issue is about the role of geographical distribution of these relations, since geographical proximity can provide important benefits for firms in accessing these sources of information and new knowledge. The aim of this paper is to examine the main factors that affect geographical distance of university-industry linkages, by analysing both sides of collaboration, the characteristics of firms and universities. Several studies show that there are important benefits related to the co-location of firms? R&D staff and academic researchers (Jaffe, 1989; Audrescht & Feldman, 1996; Arundel & Geuna, 2004; D?Este & Iamarino, 2010; De Fuentes & Dutrenit, 2014). However, recent analyses show that, several times, firms prefer to collaborate with geographically distant universities, since there are some factors that stimulate firms to go far to interact with university (D?Este & Iamarino, 2010; Laursen et al, 2011; Muscio, 2013). Hence, the main question that the literature are trying to answer is why firms go far to interact with university. General results points to two main drivers. First, firms look for distant universities when they cannot find local high-performance academic research. Second, firms must have high absorptive capacity in order to be able to search for universities that are able to solve their innovative problems. Previous studies show important evidence to this debate. However, they left an important gap that requires deeper analysis, since evidence presented in previous studies are based only on information about the university (D?Este & Iammarino, 2010; Muscio, 2013) or only of the firm (Laursen et al, 2011; De Fuentes & Dutrenit, 2014). Linked to this issue, this paper aims to contribute to this debate not only by presenting new evidence on the main drivers of the pattern of geographical distance of university-industry linkages, but also by presenting a comprehensive analysis of the collaboration by using complete information of both universities and firms. To do that, a wide-ranging database of interactions between university and industry was used in the scientific fields of Engineering and Agrarian Sciences in Brazil. Main results of the empirical analysis show that bigger firms with higher absorptive capacity tend to interact with more distant research groups, which shows the importance of the skills of the firm to find universities, local or distant, that are able to solve their innovative problems. On the side of the university, larger research groups and those who perform higher quality academic research presents higher average geographical distance of interactions, which shows that they are able to attract more distant firms to collaborate.
Keywords: R12; O18; 330